2020
DOI: 10.1039/c9ra08162c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and physicochemical behavior of a 3D hydrogel scaffold during cell growth and proliferation

Abstract: 3D cell scaffold based on macroporous PNIPAM is cytocompatible and preserves the cell viability for more than 75 culture days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…However, the resazurin-based assays are dependent on the cell metabolic state, and it is known that, in various conditions, cell metabolism can change, thus over-or under-estimation of the overall cell population might occur [18]. Assessment of the entire cellular DNA content is becoming a reliable method for cell proliferation analysis [28][29][30]. The development of a 3D compatible DNA concentration-based method was the goal of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the resazurin-based assays are dependent on the cell metabolic state, and it is known that, in various conditions, cell metabolism can change, thus over-or under-estimation of the overall cell population might occur [18]. Assessment of the entire cellular DNA content is becoming a reliable method for cell proliferation analysis [28][29][30]. The development of a 3D compatible DNA concentration-based method was the goal of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The other strategy is based on the quantification of cellular DNA and can measure cell number at the population level or even at the individual cell level [28]. These methods are generally based on stoichiometric fluorophore binding to DNA, meaning that cell number can be evaluated using fluorescent microscopy, PCR quantification, or fluorescence measurements [28][29][30]. Only several fluorophores are usually used for cell number evaluation in 2D and 3D-PicoGreen, CyQuant, and Hoechst 33258.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with our previous studies, which showed that encapsulated cell growth was proportional to the rate of scaffold swelling/degradation [ 36 , 37 ]. Furthermore, hydrogel scaffold degradation via hydrolysis over time has been shown to lead to changes in the mechanical properties of the scaffolds [ 52 ]. As such, the mechanical strength and dimensions of the scaffolds play important roles in both the restriction of colony size and the rate of cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Basic in vitro studies have shed light on mammalian cell responses (cellular adhesion, proliferation, morphogenesis, and differentiation) when growing on surfaces or into structures of biocompatible hydrogels. [ 18,19 ] Studies conducted in our laboratory show that synthetic hydrogels based on poly(N‐isopropylacrylamide) (PNIPAM) and copolymers are non‐cytotoxic, [ 20 ] feature that make them ideal candidates to work with biological samples. Adhesion and proliferation of bovine fetal fibroblasts on hydrogel surfaces [ 19–21 ] and into 3D hydrogel structures, [ 18 ] bioethanol production by encapsulated Saccharomyces cerevisiae, [ 22 ] cytotoxicity and bioadhesive properties of murine preadipose cells (3T3‐L1), human embryonic kidney cells (HEK293), and human lung carcinoma‐derived cells (A549), [ 23 ] are some of the biologic systems used to characterize the physicochemical interactions between cells and polymeric materials based on PNIPAM and copolymers.…”
Section: Introductionmentioning
confidence: 99%